Diagnostic value of shear-wave elastography for patellar tendinopathy in female volleyball and basketball athletes: a cross sectional case control study - Devran, S.; Gözübüyük, Ö. B.; Dinçer, S.; Günver, M. G.; Bayraktar, B. (The Physician and Sportsmedicine, 2024)
Objectives We aim to investigate the accuracy of shear-wave elastography (SWE) in diagnosing patellar tendinopathy in female volleyball and basketball players. In addition, we compared different parts of the patellar tendon and investigated the effects of different knee angles on elastography measurements.